開業助産師が捉えている分娩期におけるWomen-centered careとその実践 - 石引 かずみ; 家吉 望み; 加納 尚美 (日本看護科学会誌, 2023)
要旨　目的：開業助産師が捉えている分娩期におけるWomen-centered careとその実践を明らかにすること．　方法：分娩取扱のある有床助産所に3年以上勤務する助産師12名を対象に，半構造化面接にてデータを収集し質的記述的に分析した．　結果：次のコアカテゴリが生成された．【女性の生涯を見据えて分娩期を理解する】，【女性と子どもと家族を包含し，一丸となって分娩期に臨む】，【女性と子どもの「命と幸せ」を守るために自律する】ことが必要であると捉え，母子と家族の幸せのために【女性と家族への揺るぎない信念のもと行動する】ことを土台として【女性のためにあらゆる関係性を醸成する】ことに尽力しながら【女性のすべてを包容し添い続ける】ことを通し【女性が産むことに能動的になれるよう働きかける】実践であった．　結論：開業助産師の分娩期におけるWCCは，ポジティブな出産体験が女性と家族に好影響をもたらすことを認識し，それを実現するために自律した助産実践を志向していた． 　Purpose: Examine the awareness and practice of women-centered care during delivery by independent midwives.　Methods: Data were collected by conducting semi-structured interviews with 12 midwives, who had been working for at least three years at a midwifery facility. We conducted a qualitative and descriptive analysis　Results: The following core categories were generated: [understanding the delivery period from the woman's life perspective], [inclusive care for the woman, child and family], and [autonomous protection of the woman and child's well-being]. The midwives established [unwavering faith in the woman and family] as the basis for maternal and child happiness, and practiced the [encouragement of active childbirth] through [embracing womanhood and continuous support] while cultivating [comprehensive relationships for the woman].　Conclusion: Independent midwives were aware that a positive delivery experience would have a favorable impact on the woman and her family within the context of women-centered care during delivery. Thus, they were inclined toward autonomous midwifery practice to achieve this objective.